2023
DOI: 10.3390/ijerph20010883
|View full text |Cite
|
Sign up to set email alerts
|

Driving Factors and Spatiotemporal Characteristics of CO2 Emissions from Marine Fisheries in China: A Commonly Neglected Carbon-Intensive Sector

Abstract: The CO2 emissions from marine fisheries have a significant impact on marine ecology, despite generally being overlooked in studies on global climate change. Few studies have estimated the carbon emissions from marine fisheries while taking into account all pertinent sectors. This study evaluated marine fisheries’ CO2 emissions based on three sectors: marine fishing, mariculture, and the marine aquatic product processing industry. Kernel density estimation and the spatial Durbin model were used to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Liu et al (2023a) found that the social and economic system, as well as the scale of marine fishery development, are essential factors driving carbon emissions, and adjusting industry structure will inhibit marine fishery carbon emissions. What's more, Zhang et al (2023) found that the economic and trade development of marine fishery would increase CO2 emissions, and the technological progress and income growth of fishermen could reduce carbon emissions.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2023a) found that the social and economic system, as well as the scale of marine fishery development, are essential factors driving carbon emissions, and adjusting industry structure will inhibit marine fishery carbon emissions. What's more, Zhang et al (2023) found that the economic and trade development of marine fishery would increase CO2 emissions, and the technological progress and income growth of fishermen could reduce carbon emissions.…”
Section: Research Contextmentioning
confidence: 99%
“…(c) Environmental regulation (ER). Referring to the research of Zhang et al (2023), this paper selected the ratio of the power of the vessel controlled by the "dual control policy" to the power of the marine motor fishing vessel, which is closely related to marine fishery CO2 emissions, to measure the regulation intensity. (d) Level of financial development (FD).…”
Section: Measurement Of Carbon Decoupling State Of Marine Fishery (Cd...mentioning
confidence: 99%
“…Li et al (2022) accounted for China's fishery carbon emissions, carbon sinks and net carbon emissions, and used logarithmic mean decomposition index (LMDI) to analyze the impact of net carbon emissions, and it was found that carbon intensity and industrial structure were the main influencing factors. Some studies have suggested that the development of the marine fishery economy and trade have a positive driving effect on carbon emissions, the expansion of the tertiary industry does not decrease carbon emissions (Zhang et al, 2023). Guan et al (2022) also used LMDI to analyze the factors affecting carbon emissions from China's marine fisheries, and the results showed that population (the number of people engaged in the fishery) is an important inhibitory factor for the net carbon emissions of the offshore fishing industry in most coastal provinces.…”
Section: Introductionmentioning
confidence: 99%